Comportamento ingestivo de vacas Jersey em pastagens tropicais anuais - Belli, Claudinei Zucco Pitro (2011)
Knowledge of the ingestive behavior of cattle is important, since the dry matter intake is the main factor affecting animal performance. Therefore, the objective of this study was to evaluate,during the summer period, the feeding behavior of lactating cows of Jersey breed in tropical pastures consist of annual grasses, millet, sorghum and Sudan grass in the initial stages, intermediate and final the production cycle. Were evaluated specifically, the time of rumination,idleness, and their correlations with grazing pasture. The study was conducted at the experimental farm UTFPR, the area of 750 m2 was used to form a picket line, which was divided into three sidebands (250 m2) following the slope of the terrain, using a range of grass species. For the evaluation, we used six lactating cows of Jersey breed. The animals were on pasture from 8h to 16h and 18h to 6h, and its willingness shade, water and mineral salt. The observations were carried out in shifts of four hours, during 20 hours a day. The experimental design was completely randomized. The data collected were subjected to analysis of variance, used for comparison of means by Tukey test at 5% probability of error. There was statistical difference for the time grazing in sorghum and millet did not differ for sudão grass in the development stages of the species evaluated. Has been a higher mass production for sorghum forage, which was also the most grazed considering the entire production cycle of forage. Statistical differences were also observed between the developmental cycles of pastures studied for the parameters of rumination, idleness and total grazing.